STRATEGI PENGEMBANGAN PARIWISATA KOTA SEMARANG: PERSPEKTIF COLLABORATIVE GOVERNANCE SELAMA PANDEMI COVID-19 DI KAMPUNG WISATA TAMAN LELE - Fauzan Mahfuzh; Ari Subowo; Teuku u Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Semarang City is a city that has great tourism potential. There are various types of tourism in Semarang. However, during the COVID-19 pandemic, the decline in the number of tourists and the Regional Original Income (PAD) of the City of Semarang made the City of Semarang have to prepare a development strategy in order to survive. Taman Lele Tourism Village as one of the leading tourism sectors under the auspices of the Department of Culture and Tourism is expected to increase the income of the city of Semarang. This study aims to describe the collaborative governance process and the influencing factors in the development strategy of the Taman Lele Tourism Village. The results of this study indicate that the governance collaboration process carried out by the Semarang City Government, especially the Semarang City Culture and Tourism Office is quite good. However, the lack of actors to collaborate in making development strategies only involves the government and the community. This study uses qualitative methods, data collection by interviews and observations, data sources using primary and secondary data